Awakening of the Self to the Interconnectedness of Things: Stewardship and Caring for Creation through Religious Lens. Review of Religious Self-Cultivation and Environmental Flourishing: A Humanist Relational Approach, by Anthony Le Duc - Vien V. Nguyen (Studia Ecologiae et Bioethicae)
According to the SEeB policy, we do not provide abstracts for review articles.